Jason E. Taylor, Deconstructing the Monolith: The Microeconomics of the National Industrial Recovery Act - CARSON, Scott Alan (Turkish Economic Review, 2020)
Abstract. After two years of languished recovery, additional measures were needed, and within six weeks of early 1933, policy makers armed with modern economic theory developed a plan to restructure the US economy and combat the worsening Great Depression. In Reconstructing the Monolith, Jason Taylor synthesizes his and other scholar’s research to address the National Industrial Recovery Act. Keywords. Microeconomics, Nartional industrial, Monolith. JEL. B21, D00, D20, D40.